A protecting group–free approach for synthesizing C-glycosides through glycosyl dithiocarbamates. Issue 14 (24th March 2021) - Li, Gefei; Noguchi, Masato; Arisaka, Genki; Tanaka, Yuuki; Shoda, Shin-ichiro
Abstract : The first protection/deprotection-free process for radical C -glycosylation has been achieved through one-step preparable glycosyl dithiocarbamates (GDTCs). Abstract : The first protection/deprotection-free process for radical C -glycosylation has been achieved through one-step preparable glycosyl dithiocarbamates (GDTCs). The Giese-type reaction and radical allylation of unprotected GDTCs were successfully performed to obtain the corresponding α- C -glycosides stereoselectively under mild reaction conditions.